ROS 2017
DOI: 10.20455/ros.2017.853
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Reactive Oxygen Species Associates with the Achievement of Meiotic Competency in Rat Oocytes Cultured In Vitro

Abstract: Reactive oxygen species (ROS) play an important role during meiotic maturation and ovulation. The downstream impact of ROS during the achievement of meiotic competency remains ill understood. The present study was aimed to find out the impact of ROS on the level of cyclic nucleotides and maturation promoting factor (MPF) during the achievement of meiotic competency. For this purpose, cumulus oocyte complexes (COCs) were collected from the ovary of experimental rats injected with 20 IU pregnant mare's serum gon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…The CTCF analysis of fluorescence intensity of the respective egg further confirms above finding (Figure 1F3; p < 0.001). These results suggest that increased level of ROS could modulate membrane potential of internal stores resulting in the increase of cytosolic free Ca 2+ in rat eggs in vitro [2,3,5,25,26] and EM-II in rat eggs in vitro [27].…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The CTCF analysis of fluorescence intensity of the respective egg further confirms above finding (Figure 1F3; p < 0.001). These results suggest that increased level of ROS could modulate membrane potential of internal stores resulting in the increase of cytosolic free Ca 2+ in rat eggs in vitro [2,3,5,25,26] and EM-II in rat eggs in vitro [27].…”
Section: Resultsmentioning
confidence: 77%
“…However, under experimental conditions, collection of cumulus oocyte complexes (COCs), removal of cumulus cells (shear force), and other physical factors may accelerate meiotic resumption from M-II arrest and thereby SEA [22][23][24]. Although a moderate increase of ROS does not cause oxidative stress, it is good enough to modulate meiosis in rat eggs cultured in vitro [2,3,25,26]. ROS induce release of Ca 2+ from the endoplasmic reticulum [27,28].…”
mentioning
confidence: 99%
“…High ROS in the oocytes would decrease the maturation promoting factor (MPF), which ultimately leads to a decrease of oocyte competence to resume its meiotic process. As is generally known, the MPF functions to control mitosis and meiotic processes, and it also serves to induce the metaphase process in the oocyte (Tiwari and Chaube, 2017). As such, the presence of GSH during maturation acts as a gamete defense mechanism against ROS.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the culture systems increase ROS production since animal death started to culture process. The research by Tiwari and Chaube (2017) reported that in vitro culture systems could increase ROS levels in oocyte. A multitude of key factors regulate the generation of ROS in the media and include various cellular metabolic reactions, oxygen concentration, light, oocyte handling, and general physicochemical parameters that may have a negative impact on oocyte physiology by inducing apoptosis (Khazaei and Aghaz 2017).…”
Section: Discussionmentioning
confidence: 99%